2019
DOI: 10.5530/ptb.2019.5.15
|View full text |Cite
|
Sign up to set email alerts
|

Pattern use of Non-steroidal Anti-inflammatory Drugs among Saudi Community: Patients' Perspective

Abstract: Objectives: In this study, we aimed to explore the utilization of public use of non-steroidal anti-inflammatory drugs (NSAIDs) among the participants from the major metropolitan areas in Saudi Arabia. Methodology: This is a cross-sectional study conducted over a period of 6 months. The study questionnaire was randomly distributed via digital media using Survey Monkey system to individuals in the Kingdom of Saudi Arabia. The questionnaire comprised 24 questions related to demographic data; age; education; socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The prevalence of H. pylori infection and peptic ulcer is high in Saudi Arabia as it is diagnosed in around 73% of the studied Saudi patients in the Western region of the Kingdom ( Saber et al, 2015 ). On the other hand, a survey study done in the major metropolitan areas in the Kingdom including 3000 individuals showed that NSAIDs are highly consumed as daily pain killers ( Bahdailah, 2019 ). Moreover, the current gastric ulcer treatment has numerous adverse reactions as well as partial efficacy against gastric illnesses ( de Lira Mota et al, 2009 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of H. pylori infection and peptic ulcer is high in Saudi Arabia as it is diagnosed in around 73% of the studied Saudi patients in the Western region of the Kingdom ( Saber et al, 2015 ). On the other hand, a survey study done in the major metropolitan areas in the Kingdom including 3000 individuals showed that NSAIDs are highly consumed as daily pain killers ( Bahdailah, 2019 ). Moreover, the current gastric ulcer treatment has numerous adverse reactions as well as partial efficacy against gastric illnesses ( de Lira Mota et al, 2009 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NSAIDs are highly consumed in Saudi Arabia. A survey questionnaire was distributed to 3000 individuals from the major metropolitan areas in the Kingdom, and among 500 responders, 43.33% of them were took painkillers daily ( Bahdailah, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been published recently about the knowledge, awareness, and perceptions of the general Saudi population towards NSAIDs, but specific subpopulations such as pregnant women and women of childbearing age were not addressed [ 1 , 14 , 15 , 16 , 17 ]. However, two Saudi studies investigated pregnant women’s knowledge about the use of NSAIDs and other medications such as paracetamol, antacids, antibiotics, and antihistamines [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study in Saudi Arabia has assessed student's attitude and awareness toward the use of OTC in the examination. The sample size was 1,596 of the student, 829 were college students, and 767 were high school [6]. Another study, Koffeman et al, published on the high-risk use of over-thecounter nonsteroidal anti-inflammatory drugs in the Rotterdam region of the Netherlands since 2014.…”
Section: Introductionmentioning
confidence: 99%